(3eSJNdU GdEMjGA heSJNdU GdCMjGAs - (3CHh GdbGSe Hf jhSa GdMSjfj GdeOjfjs
(3ChdgG (B:s
(3jHOC HGdbSe GdChd ai GdYHGOGJ HcJGH aVjdI GdYde hGdJYdje s
(3BNQgG (B:s
(3jfJgi HNGJeI GdcJGH HHGH ai SYI QMeI Gddg JYGdi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdJUha hGdBOGH GdTQYjIs